DETERMINAN MINAT MAHASISWA BERINVESTASI PADA PASAR MODAL - Desli Desli; Mortigor Purba (LPPM Universitas Putera Batam, 2026)
This study aims to analyze the determinants of students’ interest in investing in the capital market, namely investment knowledge, capital market training, and investment motivation. This research employs a quantitative approach using a causal associative method. Primary data were collected through questionnaires distributed to 395 students in Batam City, with the sample size determined using the Slovin formula at a 5% margin of error.The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that investment knowledge, capital market training, and investment motivation partially and simultaneously have a positive and significant effect on students’ interest in investing in the capital market. The coefficient of determination (R²) value of 0.791 shows that 79.1% of the variation in students’ investment inter est can be explained by these variables, while the remaining percentage is influenced by other factors outside the research model. The findings of this study are expected to contribute to efforts to enhance students’ investment literacy and participation in the capital market.